Seismostratigraphy of the Siberian Arctic Ocean and adjacent Laptev Sea Shelf - Weigelt, Estella; Jokat, Wilfried; Franke, Dieter (2013)
The contribution presents a new seismostratigraphic model for the East Siberian part of the Arctic developed on the base of multichannel seismic reflection lines collected along a transect at 81°N. Age control for the sedimentary units was acquired via links to seismic lines and drill site data of the Canada Basin, the Lomonosov Ridge, and the adjacent Laptev Shelf. The data provide an insight into the sedimentary cover and crustal surface in which in turn tectonic and glacial processes are documented. Two distinguished seismic interfaces were mapped throughout the area, which form a crucial link between the stratigraphy of the Laptev Sea and models on the evolution of the Lomonosov Ridge. The lower one, a pronounced sequence of high-amplitude reflectors is the most striking feature in the Siberian Arctic Ocean. It indicates a strong and widespread change in deposition conditions. Probably it developed during Oligocene times when a reorientation of Arctic Plates took place, accompanied by a widespread regression of sea level. The top of the reflector band is suggested to mark the end of Oligocene, and consequently the sedimentary sequences above are younger than 23 Ma. The upper interface parallels the seafloor in a depth of about 200ms. It is marked by a change from a partly transparent sequence with weak amplitude reflections below to a set of continuous high-amplitude reflectors above. The high amplitudes indicate a strong alternation in deposition conditions. Likely this interface marks the transition to large-scale glaciation of the northern hemisphere, and consequently is dated to top of Miocene (5.3 Ma).